Androgenic and estrogenic modulation in the prostate: an approach in rodent experimental models with emphasis on structural biology - Taboga, Sebastião Roberto [UNESP]; Vilamaior, Patricia Simone Leite; Góes, Rejane Maira (My University, 2009)
The endocrine system is a complex network of glands and hormones that regulates many of the body's functions; including growth, development and maturation, as well as the way several organs operate. The prostate is an important target of hormones and its functional maturity and development are influenced by steroids levels. Our research group has been evaluating the potential effects of the steroidal agents on the Mongolian gerbil (Meriones unguiculatus) male and female prostate using different morphological and immunohistochemical methods. Our results have revealed the Mongolian gerbil prostate as an important tool for the morphofunctional studies of steroid hormones and its antagonist actions.
Modulação androgênica e estrogênica na próstata: uma abordagem em modelos experimentais de roedores com enfoque na biologia estrutural.